Thermochemistry and kinetics of graphite oxide exothermic decomposition for safety in large-scale storage and processing. (January 2016) - Qiu, Yang; Collin, Felten; Hurt, Robert H.; Külaots, Indrek
Abstract: The success of graphene technologies will require the development of safe and cost-effective nano-manufacturing methods. Special safety issues arise for manufacturing routes based on graphite oxide (GO) as an intermediate due to its energetic behavior. This article presents a detailed thermochemical and kinetic study of GO exothermic decomposition designed to identify the conditions and material compositions that avoid explosive events during storage and processing at large scale. It is shown that GO becomes more reactive for thermal decomposition when it is pretreated with OH − in suspension and the effect is reversible by back-titration to low pH. This OH − effect can lower the decomposition reaction exotherm onset temperature by up to 50 degrees of Celsius, causing overlap with common drying operations (100–120 °C) and possible self-heating and thermal runaway during processing. Spectroscopic and modeling evidence suggest epoxide groups are primarily responsible for the energetic behavior, and epoxy ring opening/closing reactions are offered as an explanation for the reversible effects of pH on decomposition kinetics and enthalpies. A quantitative kinetic model is developed for GO thermal decomposition and used in a series of case studies to predict the storage conditions under which spontaneous self-heating, thermal runaway, and explosions can be avoided.